The internationalization of TCM towards Portuguese-speaking countries - Xiaoting Zheng; Liyang Lyu; Hong Lu; Yuanjia Hu; Ging Chan (BMC, 2021)
Abstract With the increasing demand for traditional Chinese medicine (TCM) in Portuguese-speaking countries (PSC), local regulatory systems and relevant legislation are still insufficient and lagging, even blank in some of them. This kind of unbalanced pace either makes users of TCM exposed in potential risk or eventually obstructs the long-term development of TCM in PSC. Despite existing tremendous studies on the internationalization of TCM, there are few studies specific to PSC. Thus, by a comprehensive desk review and typical case study, this article aims to summarize current situation of TCM in PSC by a cross-regional comparison, to identify various critical challenges, and further to provide an insightful reference to impel the development of TCM in PSC.